Accumulation of dry mass, N, P and K in different genetic sources of Conilon coffee - Prezotti, Luiz Carlos; Bragança, Scheilla Marina (Coffee Science - ISSN 1984-3909, 2014)
To expand the knowledge base concerning nutrition of conilon coffee, this work was developed to determine the dry mass and macro and micronutrient accumulation of different genetic sources of conilon coffee. The genetic sources used for the study were: EMCAPER 8151 (a cultivar propagated by seed) and clones 02, 03, 14, 23 and 120. During the first five years after planting, entire plants of each genetic material were collected monthly, divided into parts (leaves, branches, stem, root, and fruit), and the amount of dry matter (biomass) and the nutrient content were determined. On the basis of these data the nutrient content in each part of the plants as a function of age was estimated. The 02 and 23 clones produced the largest amount of dry mass of leaves, and clone 23 showed greater accumulation of dry mass of vegetative part. The largest fruit dry mass production was the clone 02, followed by clone 120. The ratios of the averages of the dry mass of leaf, twig, stem, root and fruit of genetic material were 19%, 12%, 42%, 15% and 12%, respectively. Contents of N, P and K in all parts of the plants declines over the months after flowering. Clone 23 showed the highest rate of accumulation of N (0.09298 g-1 plant-1 day-1) and clone 14 presented the lower rate of accumulation (0.04696 g plant-1 day-1). Clone 02 showed the highest rate of accumulation of P (0.01483 g plant-1 day-1) and the EMCAPER 8151 showed the highest rate of accumulation of K (0.04919 g plant-1 day-1). The accumulated nutrients content in various parts of plants genetic material is atributed mainly to differences in dry mass production than to differences in nutrient levels.